A Case Study Of Malayan Banking Berhad (Maybank Group) - Ramasamy, Tamilzchelvi (2005)
The case study is to identify the strategic issues faced by Maybank as well as to discover the current strategies used by the Group. Analyzing the present performance and further improve the performance of the Group need to be done accordingly through application of various techniques, evaluation and action plan. Based on the result, recommendation will be made to further enhance the credibility and ability of the Group.